2021
DOI: 10.1101/2021.07.01.21259687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Seroprevalence of anti-SARS-CoV-2 antibodies among Ethiopian healthcare workers

Abstract: COVID-19 pandemic has a devastating impact on the economies and health care system of sub-Saharan Africa. Healthcare workers (HWs), the main actors of the health system, are at higher-risk because of their occupation. Serology-based estaimates of SARS-CoV-2 infection among HWs represent a measure of HWs level of exposure to the virus and a guide to the prevalence of SARS-CoV-2 in the community. This information is currently lacking in Ethiopia. This study aims to develop an in-house antibody testing assay and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This could be explained by a multitude of interlinking factors. High levels of asymptomatic cases, both for the general population and HCWs, have been documented in African as well as global studies 11 17–21. As our study’s active infection testing selected suspected cases of COVID-19 only, we could have missed a large proportion of asymptomatic cases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This could be explained by a multitude of interlinking factors. High levels of asymptomatic cases, both for the general population and HCWs, have been documented in African as well as global studies 11 17–21. As our study’s active infection testing selected suspected cases of COVID-19 only, we could have missed a large proportion of asymptomatic cases.…”
Section: Discussionmentioning
confidence: 94%
“…A recent Zambian postmortem study suggested that many people who die have an undiagnosed SARS-CoV-2 infection 4. Various studies have determined the seroprevalence in Africa 5–13. A recent systematic review has estimated it to be approximately 22%, with highest seroprevalence in central Africa 5.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, a study conducted in 5 different hospitals in Ethiopia showed 39.6% seropositivity for COVID-19 among 1997 HCWs. 13 Also, similar studies conducted among HCWs in Somalia and Egypt showed high rate of COVID-19 transmission. 14,15 Nonetheless, considering that this is a novel infection with transmission patterns and sources yet to be fully understood, it is expected that the risk of infection might be significantly high within such frontline centres.…”
Section: Discussionmentioning
confidence: 87%
“…After screening 38 studies (Figure 1) and excluding 16 (Supplementary references), 22 studies were eligible (18 retrieved from the main search and another 4 retrieved from cited/citation searches). [3][4][5][6][7][8][9][10][11][12][13][14][22][23][24][25][26][27][28][29][30][31] 19 studies were published in peer-reviewed journals and 3 were preprints. Other studies screened in-depth and excluded are shown in Supplementary References along with the reason for exclusion.…”
Section: Eligible Studiesmentioning
confidence: 99%